The actuarial balance sheet for pay-as-you-go finance: solvency indicators for Spain and Sweden - Maria del Carmen Boado-Penas; Salvador Valdés-Prieto; Carlos Vidal-Meliá (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper provides the first estimate of the actuarial balance of the Spanish contributory pension system for the old age contingency, based on official data. The novel entry in the balance sheet, named Contribution Asset or Hidden Asset, is at the centre of the theoretical discussion. A comparison between the official balance sheet for the Swedish national account system and our balance sheet for the Spanish system is also provided. The main finding is that the Spanish pension system has an insolvency rate of 31.4 %. The policy implication is that unless current legislation is reformed, Spanish taxpayers (the plan sponsor) should count on making transfers to the pension system with a present discounted value of 31.4 % of current liabilities. Moreover, a comparison of the consecutive balance sheets for 2001-06 shows that the degree of insolvency is growing over time, even though the cash-flow outcome has improved over the same period. Taking steps to reverse this trend and restore solvency is in the Spanish taxpayers' interest, and possibly also in the interest of those in the European Union who recognise that there is a chance that they may have to support the Spanish budget in the future.
Keywords: H55; J26; M49; 330; retirement; pay-as-you-go system; accountancy; solvency; pensions; Spain